The Practical Forms and Challenges of Administrative Governance at the Village Level - Wei, Tongyue (Journal of Social Science and Humanities, 2024)
In the context of advancing the modernization of grassroots governance systems and capabilities, the administrative approach to village-level governance has emerged as a significant trend in the transformation towards modernized grassroots governance. The internal resource scarcity within rural areas, the gradual disintegration of familiar social networks, and the necessity for the transformation of governance services and the enhancement of governance capabilities have provided both impetus and a solid foundation for the administrative approach to village governance. Currently, the administrative nature of village governance is primarily reflected in the professionalization of village officials, the bureaucratization of village organizations, and the standardization of work processes. While this administrative approach can enhance administrative efficiency and improve the assessment of village organizations by grassroots governments, it also faces challenges such as the imbalance in the relationship among "strong administration, weak autonomy," and the dynamics between villagers, village officials, and township governments. Additionally, there are real issues regarding the responsiveness and public nature of village organizations. To some extent, this can interfere with village officials' governance of rural areas, particularly when individual officials prioritize personal gain over addressing villagers' needs, focusing on form rather than genuinely resolving issues. Over time, this may lead to a loss of trust among villagers towards their officials, which is detrimental to the sustainable development of rural governance.